STRATEGI PENGEMBANGAN MINAWISATA DI TELUK SAWAI KABUPATEN MALUKU TENGAH - Lolita Tuhumena; Sara Umbekna; Parina Sella; Yvonne I. Pattinaja; Leopold A. Tomasila (PAPALELE: Jurnal Penelitian Sosial Ekonomi Perikanan dan Kelautan, 2022)
The waters of the bay are known among domestic and foreign tourists as a tourist destination. Various tourist objects and attractions that offer beautiful beaches, underwater diving, waterfalls and natural cave holes are in this region. With the increasing activity of tourism and local community activities, it is certain that in the next few years almost all of the land will be used for various development activities, so the need for efficient utilization of coastal and marine resources, especially the utilization of fisheries and tourism potentials by developing the concept of minawisata in the area. The research purpose was formulating the development strategy of minatourism in Sawai Bay. The study was conducted for 3 months from September to November 2020. The data collection used primary and secondary data as well as purposive sampling. The data analysis method SWOT and AHP. The results showed that The priority strategies for developing minatourism in Sawai Bay, Central Maluku Regency; Development of quality human resources in the community; Increasing public awareness around the Sawai Bay area of ​​the importance of protecting fisheries and marine environmental resources; Developing local community expertise to support minatourism activities; Increasing tourism facilities and infrastructure; Increase the promotion of online/offline minawisata; Increase cooperation between managers and investors; and Improve MCS (monitoring, controling, survellance) (0.0058).